2024
DOI: 10.1001/jamacardio.2023.5372
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Multicenter Risk Model to Predict Right Ventricular Failure After Mechanical Circulatory Support

Iosif Taleb,
Christos P. Kyriakopoulos,
Robyn Fong
et al.

Abstract: ImportanceThe existing models predicting right ventricular failure (RVF) after durable left ventricular assist device (LVAD) support might be limited, partly due to lack of external validation, marginal predictive power, and absence of intraoperative characteristics.ObjectiveTo derive and validate a risk model to predict RVF after LVAD implantation.Design, Setting, and ParticipantsThis was a hybrid prospective-retrospective multicenter cohort study conducted from April 2008 to July 2019 of patients with advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A list of selected AI-driven studies is shown in Table 1B. Most recently published is the STOP-RVF study, which generates a risk assessment tool for the prediction of right ventricular failure and consequent mortality [50]. This is a supervised machine learning model with a c-statistic of 0.73-0.75.…”
Section: Ai Models For Durable Mcs and Their Limitationsmentioning
confidence: 99%
“…A list of selected AI-driven studies is shown in Table 1B. Most recently published is the STOP-RVF study, which generates a risk assessment tool for the prediction of right ventricular failure and consequent mortality [50]. This is a supervised machine learning model with a c-statistic of 0.73-0.75.…”
Section: Ai Models For Durable Mcs and Their Limitationsmentioning
confidence: 99%